Kajian Terhadap Unjuk Kerja Bangunan Pengaman Pantai Dengan Penerapan Simulasi Numerik One Line Model - Dalrino - -; Elvi Roza Syofyan (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2015)
With the position on the west coast region of Sumatra, Padang beach facing directly to Indian Ocean that have potentially threat by the ocean waves that relatively give effect to changes in the coastline. This study was conducted to evaluating the performance of existing coastal protection structure to restrain the rate of erosion as a result of the influence of hydrodynamics process. Condition that reviewed was in form of distance shoreline as simulation results to initial reference line before. One Line Model was conducted to get shoreline change in each time step calculation. Model consists of two conditions, with the absence of coastal structures and with structure respectively. The simulation result show that potential erosion occurs at Batang Arau river mouth with no protection structure. Large erosion predicted around 59.04 meters from the shoreline position early. With coastal protection, model result obtained sedimentation of 7.33 meters coastline from its initial position. This occurs at a distance of 475 meters from the boundary domain. Modeling results also showed erosion is 18.39 meters at a distance of 250 m from the boundary domain. This is likely due to the limited modeling conditions that without reviewing of littoral transport direction that occurred in perpendicular to the coast. Result study show that the presence of a groyne in Padang coasts looks already quite effective in defense of the shoreline of the littoral transport direction, however the installation of groins seemingly did not give significant meaning in the addition of the coastline